MATHEMATICAL MODELS OF HALF-RING PHOTORESISTIVE CONVERTERS OF VANE TURNING ANGLES - O. S. Rayimjonova (European Science Publishing, 2023)
In the design of the heat exchanger for flows, the turning rod of the vane is located between the fixed upper and lower half-ring photoresistors connected to the ring pushed 90 degrees from each other, and between the ring radiation sources and receivers, fixed to the wall of the vane, there are two identical half-disc optical screens, which are covered with a constant ring radiation source.
Keywords: aileron pivot, and half-ring photoresistors, turning angle, two identical half-disc optical screens.